2020
DOI: 10.1111/bcp.14338
|View full text |Cite
|
Sign up to set email alerts
|

Scientifically based combination therapies with immuno‐oncology checkpoint inhibitors

Abstract: The discovery of immune checkpoints and their role in modulating immune response have revolutionised cancer treatment in recent years. The immune checkpoints, cytotoxic T‐lymphocyte‐associated protein 4, programmed cell death protein 1 and its ligand, programmed cell death‐ligand 1, have been extensively studied. Currently 7 monoclonal antibodies targeting these immune checkpoints are approved for treatment of various cancers. Inhibiting immune checkpoints has shown some success in clinic, however, a proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 179 publications
(203 reference statements)
0
1
0
Order By: Relevance
“…The discovery and development of immune checkpoint inhibitors, cytotoxic T‐lymphocyte‐associated protein 4 (CTLA‐4) inhibitors, programmed cell death protein 1 (PD‐1) inhibitors , and programmed cell death‐ligand 1 (PD‐L1) inhibitors are comprehensively reviewed by Chew et al 7 These authors noted that some of these agents have shown a wide range of benefits but also considerable toxicities in the clinic and emphasize that many patients with solid tumours do not benefit. Although immunotherapy agent dosing is still being optimized, Chew et al note that as well as anti‐CTLA‐4 and anti‐PD‐1, there are several other inhibitory membrane proteins involved in regulating the immune response which could be targeted.…”
mentioning
confidence: 99%
“…The discovery and development of immune checkpoint inhibitors, cytotoxic T‐lymphocyte‐associated protein 4 (CTLA‐4) inhibitors, programmed cell death protein 1 (PD‐1) inhibitors , and programmed cell death‐ligand 1 (PD‐L1) inhibitors are comprehensively reviewed by Chew et al 7 These authors noted that some of these agents have shown a wide range of benefits but also considerable toxicities in the clinic and emphasize that many patients with solid tumours do not benefit. Although immunotherapy agent dosing is still being optimized, Chew et al note that as well as anti‐CTLA‐4 and anti‐PD‐1, there are several other inhibitory membrane proteins involved in regulating the immune response which could be targeted.…”
mentioning
confidence: 99%